Assessing interlimb asymmetries: are we heading in the right direction? - dos Santos, T.; Thomas, C.; Jones, P. A. (Strength and Conditioning Journal, 2021)
The investigation of interlimb asymmetries has increased in recent years, with practitioners and researchers typically exploring the impact of interlimb asymmetry on athletic performance, screening interlimb asymmetry in relation to injury risk, and monitoring of interlimb asymmetry during injury rehabilitation. A contentious issue regarding the profiling of interlimb asymmetry is the use of thresholds to determine whether an athlete displays a "meaningful" or potentially "problematic" asymmetry and how to interpret such data. This article aims to outline the potential options available for practitioners and researchers regarding the quantification, monitoring, and interpretation of interlimb asymmetries. A video abstract is available for this article (http://links.lww.com/SCJ/A296).